2010
DOI: 10.2165/11316130-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in HIV-Positive Women

Abstract: Breastfeeding remains a common practice in parts of the world where the burden of HIV is highest and the fewest alternative feeding options exist. The impossible dilemma faced by HIV-positive mothers is whether to breastfeed their infants in keeping with cultural norms but in doing so risk transmitting the virus through breast milk, or to pursue formula feeding, which comes with its own set of risks, including a higher rate of infant mortality from diarrheal illnesses, while reducing transmission of HIV. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…[1] Among Malawian infants, the monthly incidence of HIV infection acquired via breastfeeding was 0.7%, 0.6% and 0.3% at ages 1-5, 6-11 and 12-17 months, respectively. [1] Among Malawian infants, the monthly incidence of HIV infection acquired via breastfeeding was 0.7%, 0.6% and 0.3% at ages 1-5, 6-11 and 12-17 months, respectively.…”
Section: When Is the Transmission Risk Highest?mentioning
confidence: 94%
See 3 more Smart Citations
“…[1] Among Malawian infants, the monthly incidence of HIV infection acquired via breastfeeding was 0.7%, 0.6% and 0.3% at ages 1-5, 6-11 and 12-17 months, respectively. [1] Among Malawian infants, the monthly incidence of HIV infection acquired via breastfeeding was 0.7%, 0.6% and 0.3% at ages 1-5, 6-11 and 12-17 months, respectively.…”
Section: When Is the Transmission Risk Highest?mentioning
confidence: 94%
“…[1] It is also important to note that the risk of HIV transmission appears higher with mixed feeding (i.e. [1] It is also important to note that the risk of HIV transmission appears higher with mixed feeding (i.e.…”
Section: When Is the Transmission Risk Highest?mentioning
confidence: 99%
See 2 more Smart Citations
“…Kourtis et al (2013) demonstrated that 'disruption in intestinal integrity is a mechanism of HIV transmission to infants through breast-feeding'. Furthermore, Slater, Stringer and Stringer (2010) maintain that most of women in rural and remote areas in Africa are expected by cultural norms to breast-feed their infants, thereby risking transmitting the virus through breast-milk.…”
Section: Someone Who Is Infected With Hiv But Does Not Yet Have Full-mentioning
confidence: 99%